2011
DOI: 10.2478/v10045-011-0061-5
|View full text |Cite
|
Sign up to set email alerts
|

Mutation at Codon 198 Of Tub2 Gene for Carbendazim Resistance in Colletotrichum Gloeosporioides Causing Mango Anthracnose in Thailand

Abstract: Screening of field isolates of Colletotrichum gloeosporioides from various mango cultivars from markets and orchards in Thailand identified 113 carbendazim-resistant isolates. Isolates with a highly-resistant phenotype (HR) grew well on Potato Dextrose Agar (PDA) amended with carbendazim even at ≥500 mg/l. Isolates with carbendazim-resistant phenotype had a conspicuous mutation at a particular site in the β-tubulin (TUB2) gene sequence. The sequence of TUB2 in HR isolates showed a single nucleotide transversio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 41 publications
(91 reference statements)
0
7
0
Order By: Relevance
“…Most of the molecular studies on benzimidazole‐resistant phytopathogenic fungi have focused on the replacement of amino acids at codon 198 and/or 200 in the β‐tubulin locus (Fujimura et al ., ; Koenraadt & Jones, ; Yarden & Katan, ; Davidson et al ., ; Schmidt et al ., ; Kongtragoul et al ., ). A similar mutation at codon 198 has been reported in NaNO 2 ‐induced benomyl‐resistant mutants of B. bassiana (Butters et al ., ; Zou et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…Most of the molecular studies on benzimidazole‐resistant phytopathogenic fungi have focused on the replacement of amino acids at codon 198 and/or 200 in the β‐tubulin locus (Fujimura et al ., ; Koenraadt & Jones, ; Yarden & Katan, ; Davidson et al ., ; Schmidt et al ., ; Kongtragoul et al ., ). A similar mutation at codon 198 has been reported in NaNO 2 ‐induced benomyl‐resistant mutants of B. bassiana (Butters et al ., ; Zou et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…However, previous research of the mutant target sites in the β‐tubulin genes from various phytopathogens has often shown changes at codons 6, 50, 167, 198, 200 and/or 240, and such mutations could cause benzimidazole‐resistance due to reduction of affinity to the fungicide (Ma & Michilides, ). Analyses of the target amino acids for benzimidazole‐resistance identified condon 198 and/or 200 in the β‐tubulin gene as the most common mutation sites, and these particular mutations, have been identified in several fungi including Botrytis cinerea (Luck & Gillings, ; Yarden & Katan, ; Zhang, Liu, & Zhu, ; Ziogas, Nikou, Markoglou, Malandrakis, & Vontas, ), Cercospora beticola (Davidson, Hanson, Franc, & Panella, ), Colletotrichum gloeosporioides (Buhr & Dickman, ; Kongtragoul, Nalumpang, Miyamoto, Izumi, & Akimitsu, ; Maymon, Zveibil, Pivonia, Minz, & Freeman, ) , Cercospora lactucae‐sativae (Suwan, Nuandee, Akimitsu, & Nalumpang, ) , Gibberella zeae (Liu, Yin, Wu, Jiang, & Ma, ), Helminthosporium solani (Cunha & Rizzo, ; McKay & Cooke, ), Monilinia fructicola (Koenraadt et al., ; Ma, Yoshimura, & Michailides, ), Mycosphaerella fijiensis (Cańas‐Gutiérrez, Patińo, Rodriguez‐Arango, & Arango, ), Neurospora crassa (Fujimura, Oeda, Inoue, & Kato, ), Penicillium aurantiogriseum (Koenraadt et al., ), Penicillium expansum (Baraldi et al., ; Koenraadt et al., ), Penicillium italicum (Koenraadt et al., ), Sclerotinia homoeocarpa (Koenraadt et al., ), Tapesia yallundae, T. acuformis (Albertini, Gredt, & Leroux, ), Venturia inaeqalis and V. pirina (Koenraadt et al., ). Interestingly, unlike with the aforementioned fungi, this study found that point mutations occurred at codons 79 and 102 of the β‐tubulin gene in all carbendazim‐resistant field isolates of Pestiolotiopsis sp.…”
Section: Discussionmentioning
confidence: 99%
“…Benzimidazole fungicides including benomyl, carbendazim, fuberidazole, thiabendazole, thiophanate and thiophanate methyl were introduced in the 1960s and 1970s and were among the first broad‐spectrum plant disease control agents, providing excellent preventive, curative and systemic activities (Hewitt, ; Rollinson, Marroni, & Butler, ). In Thailand, carbendazim controlled pathogens of various plants, but its widespread and extensive use led to the development of resistance in many pathosystems including Colletotrichum gloeosporioides causing mango anthracnose (Kongtragoul et al., ) and Cercospora lactucae‐sativae causing leaf spot on lettuce (Suwan et al., ). Furthermore, previous studies have reported the occurrence of benzimidazole‐resistant strains of Pestalotiopsis longiseta the causal agent of grey blight in tea fields of Kagoshima Prefecture, Japan (Omatsu, Tomihama, & Nonaka, ) and that development of resistance to benzimidazole fungicides is linked to routine applications over time (Hewitt, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations